(untitled) (Journal of Human Sciences, 2025)
The researcher has conducted a scientific study entitled The Role of University Youth in Achieving National Reconciliation in University, Al Wahat region located in the south-east of Libya. The study aimed to achieve several objectives, including identifying the role of university youth in achieving national reconciliation in university colleges located in Al Wahat, and identifying the differences between Youth by gender, specialization, and age in achieving national reconciliation. The study sample consisted of 161 university youth in the Al Wahat region, using a proportional stratified random sampling method of 10% of the population size. The descriptive approach was used in this study, and a study tool prepared by Saleh and Abu Ghalia 2016. The statistical data was analyzed using (SPSS) and the study reached several results, the most important of which is that the role of youth is positive in national reconciliation to a degree higher than the hypothesized average of the scale, and that there are no differences attributable to the variables of gender, specialization, and age, on the scale used in the study.